IMPACT OF DEMONSTRATIVE TEETH BRUSHING METHOD ON STUDENT BEHAVIOR AND DENTAL HYGIENE - Rahayu, Eka Sri; Mufizarni; Reca (Jurnal Ilmiah Keperawatan, 2024)
Introduction: The mastery of proper tooth-brushing techniques plays a pivotal role in upholding oral health standards. This research underscores the impact of demonstrative teeth brushing method on student behavior and dental hygiene among fourth-grade students at SDN 2 Lamcot in Kabupaten Aceh Besar. Methods: Employing a quasi-experimental design with an equivalent control group, the study conducted pre-test and post-test evaluations.The research incorporated a total of 60 children, distributed into an intervention group and a control group. Quantitative data analysis was conducted through paired samples t-test and Independent T-test. Results:The results exhibited statistically significant disparities (p <0.05) in mean values of knowledge, attitudes, behaviors, and Oral Hygiene Index-Simplified (OHI-S) scores immediately post-intervention and one month later between the treatment and control groups. Conclusion: Emphasizing the importance of parental involvement in dental health education programs, the study stresses the need for parental knowledge and resources to reinforce and monitor children's dental health practices at home.